When Will War For Peace Begin in Nigeria? - Alao, David Oladimeji; Iyanda, Rachael (NIU Journal of Humanities, 2017)
Nigeria since independence in 1960 has not witness an enduring peace as conflicts, crises, militancy and terrorism complicated the task of nation building. Many policies by past governments ranging from state and local creation and federal character policy as well as declaration of unlimited wars against hunger, poverty and indiscipline have not guaranteed lasting peace. The scenario informed the study to examine when war for peace will genuinely commence and the preconditions enduring peace. The paper was descriptive and made use of secondary sources of data inclusive of text books, journal, Internet materials and official documents from government circle. The study argued that there has been too much rhetoric on modalities for peace without the required political will. The study found that poor governance has made political religious and ethnicity thrives while corruption robs the citizenry of dividend of democracy. It recommended true federalism and genuine war against poverty and unemployment as well as massive infrastructural development as components of war for peace. In addition, government should embark on early monitoring of conflicts, probe the remote causes and be fair and just in transforming conflicts. The study concluded that the war for peace is insurmountable given that the right institutional and attitudinal framework is judiciously put in place and executed. Keywords: War for peace, conflict, poverty, true federalism and good governance